Optimizing aeration rates via bio-methane potential test for enhanced biodrying efficiency of refuse-derived fuel-3 - Wahyanti, Eka; Towprayoon, Sirintornthep; Sutthasil, Noppharit; Patumsawad, Suthum; Wangyao, Komsilp (Center of Biomass & Renewable Energy (CBIORE), 2024)
Aeration forms a critical part of the biodrying of refuse-derived fuel-3 (RDF-3) and significantly affects the fuel’s energy potential. Understanding the organic content (OC) of RDF-3 is crucial for determining the optimal aeration strategy. In this study, we conducted a bio-methane potential (BMP) test to estimate the OC by observing the conversion of organic matter into methane (CH₄) and carbon dioxide (CO₂). The observation of BMP was conducted using anaerobic digestion approach where substrate and inoculum are important parameters considered for the success of this test. Various ratios substrate-to-inoculum (S/I) were explored to assess their impact on biogas production, our research involved testing four S/I ratios (0.25, 0.5, 1.0, and 1.5) focusing on identifying the optimal aeration strategy. Based on stoichiometric calculations, the sample’s biogas yield per gram volatile solid indicates RDF-3’s OC is 1.5%. This OC value played a role in establishing the appropriate aeration rate (AR) for the biodrying process, which was determined to be 0.6 m³/kg.day, indicating the action of effective microbial degradation processes. Ensuring the correct AR is vital for maximizing the energy potential of RDF-3. Implementing optimized aeration rates based on the BMP test in waste management practices can significantly improve RDF-3 biodrying efficiency. This approach enhances RDF quality, reduces moisture, increases calorific value, and minimizes greenhouse gas emissions, leading to more sustainable and efficient waste-to-energy conversion.